New Aspects in the Diagnosis and Therapy of Fetal Hypoplastic Left Heart Syndrome - Graupner, Oliver; Enzensberger, Christian; Axt-Fliedner, Roland (Geburtshilfe und Frauenheilkunde, 2019)
Fetal hypoplastic left heart syndrome (HLHS) is a severe congenital heart disease with a lethal prognosis without postnatal therapeutic intervention or surgery. The aim of this article is to give a brief overview of new findings in the field of prenatal diagnosis and the therapy of HLHS. As cardiac output in HLHS children depends on the right ventricle (RV), prenatal assessment of fetal RV function is of interest to predict poor functional RV status before the RV becomes the systemic ventricle. Prenatal cardiac interventions such as fetal aortic valvuloplasty and non-invasive procedures such as maternal hyperoxygenation seem to be promising treatment options but will need to be evaluated with regard to long-term outcomes. Novel approaches such as stem cell therapy or neuroprotection provide important clues about the complexity of the disease. New aspects in diagnostics and therapy of HLHS show the potential of a targeted prenatal treatment planning. This could be used to optimize parental counseling as well as pre- and postnatal management of affected children.
Keywords: fetal hypoplastic left heart syndrome; fetal cardiac function; fetal cardiac interventions